Computational modelling reveals contrasting effects on reinforcement learning and cognitive flexibility in stimulant use disorder and obsessive-compulsive disorder: remediating effects of dopaminergic D2/3 receptor agents - Kanen, Jonathan W. (Psychopharmacology (Berl), 2019)
RATIONALE: Disorders of compulsivity such as stimulant use disorder (SUD) and obsessive-compulsive disorder (OCD) are characterised by deficits in behavioural flexibility, some of which have been captured using probabilistic reversal learning (PRL) paradigms. OBJECTIVES: This study used computational modelling to characterise the reinforcement learning processes underlying patterns of PRL behaviour observed in SUD and OCD and to show how the dopamine D(2/3) receptor agonist pramipexole and the D(2/3) antagonist amisulpride affected these responses. METHODS: We applied a hierarchical Bayesian method to PRL data across three groups: individuals with SUD, OCD, and healthy controls. Participants completed three sessions where they received placebo, pramipexole, and amisulpride, in a double-blind placebo-controlled, randomised design. We compared seven models using a bridge sampling estimate of the marginal likelihood. RESULTS: Stimulus-bound perseveration, a measure of the degree to which participants responded to the same stimulus as before irrespective of outcome, was significantly increased in SUD, but decreased in OCD, compared to controls (on placebo). Individuals with SUD also exhibited reduced reward-driven learning, whilst both the SUD and OCD groups showed increased learning from punishment (nonreward). Pramipexole and amisulpride had similar effects on the control and OCD groups; both increased punishment-driven learning. These D(2/3)-modulating drugs affected the SUD group differently, remediating reward-driven learning and reducing aspects of perseverative behaviour, amongst other effects. CONCLUSIONS: We provide a parsimonious computational account of how perseverative tendencies and reward- and punishment-driven learning differentially contribute to PRL in SUD and OCD. D(2/3) agents modulated these processes and remediated deficits in SUD in particular, which may inform therapeutic effects. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00213-019-05325-w) contains supplementary material, which is available to authorized users.